Classroom Management According to Marzano’s Comprehensive Approach to Arabic Language Teaching (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Effective classroom management is a key component in ensuring the smooth running of the learning process and improving the quality of student learning. In achieving this, teachers are expected not only to act as conveyors of subject matter, but also as classroom managers who effectively oversee the learning process. This study aims to explore in depth classroom management in Arabic language learning using Marzano's perspective. This study was conducted at Ma'had Al-Izzah Leadership School in Batu, East Java. The research focused on the four main components of classroom management and their application in Arabic language learning. This study employed a qualitative case study approach. Data triangulation was carried out to ensure the validity and reliability of the data. Subsequently, the collected data were analyzed in three stages using the Miles and Huberman framework: data reduction, data presentation, and drawing conclusions. The results of this study indicate that Marzano's comprehensive approach is highly relevant and effective in Arabic language learning and significantly improves classroom management and learning outcomes.